Sales Growth dan Leverage dalam Firm Value Subsektor Food and Beverage (JFAS : Journal of Finance and Accounting Studies, 2024)
This study aims to present empirical evidence regarding sales growth and leverage which have an effect on firm value with tax avoidance as a moderating variable. This type of research is quantitative with a purposive sampling method and the object of research is companies listed on the Indonesia Stock Exchange during the 2019-2021 period, namely the food and beverage subsector. Descriptive statistical analysis and data testing using SmartPLS 4.0.9.2 software became a research analysis technique. Hypothesis testing in this study resulted in sales growth variables influencing firm value, leverage having no effect on firm value, and tax avoidance being unable to moderate sales growth and leverage on firm value.